The early school leaving in Spain - Faci Lucia, Fernando (Avances en Supervisión Educativa, 2011)
This article is a review of the current situation with early school leavers (ESL) in Spain. It analyses the value of this indicator and its use within the European Union. The author presents an overview of the European guidelines since 2000 and the poor performance of Spain. The article gives a panoramic view on the situation, it outlines the measures which are still to be taken, and identifies the challenges that the European Union will face in the upcoming years. Finally the author offers a concluding reflexion on the subject, and gives his recommendations for achieving best results in the reduction of the ESL.